LANGUAGE LEARNING STRATEGIES FOR UNIVERSITY STUDENTS WITH ATTENTION DEFICIT DISORDER (ADD) - Santana-Quintana, M. Cristina (2017)
This paper highlights the importance of language learning strategies (LLS) as support methods related to inclusive education (IE) processes, and tries to find specific language teaching strategies for students with attention deficit disorder (ADD) in order to achieve a meaningful and functional learning. After analyzing the LLS and taking into account the difficulties learners with ADD face when learning foreing languages, we reach the conclusion that the most appropriate are the compensation and affective or socioaffective strategies, since these specific education strategies enhance their skills performance, make them part of the teaching-learning process and prepare them to make their own interventions, eliminating the stress of a regular day-to-day class, catching their attention and increasing their motivation.